2018
DOI: 10.7554/elife.32373
|View full text |Cite|
|
Sign up to set email alerts
|

Embryonic and postnatal neurogenesis produce functionally distinct subclasses of dopaminergic neuron

Abstract: Most neurogenesis in the mammalian brain is completed embryonically, but in certain areas the production of neurons continues throughout postnatal life. The functional properties of mature postnatally generated neurons often match those of their embryonically produced counterparts. However, we show here that in the olfactory bulb (OB), embryonic and postnatal neurogenesis produce functionally distinct subpopulations of dopaminergic (DA) neurons. We define two subclasses of OB DA neuron by the presence or absen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(98 citation statements)
references
References 123 publications
(196 reference statements)
17
74
0
Order By: Relevance
“…we observed a wide distribution of neuronal areas for these DA neurons (Figure 2H), which coincides with previous findings that OB DA neuron subtypes may be distinguished by their size (Pignatelli et al, 2005;Kosaka and Kosaka, 2009;Chand et al, 2015;Pignatelli and Belluzzi, 2017;Galliano et al, 2018;Kosaka et al, 2019). Given the previous findings (Halász et al, 1981;Pignatelli et al, 2005;Kosaka and Kosaka, 2007) of differences in soma sizes between two potential populations of OB DA neurons and our finding that neuronal areas of DA neurons are widely distributed (Figure 2H), we also compared these same properties between recorded DA neurons with different sizes ( Table 2).…”
Section: Membrane Propertiessupporting
confidence: 90%
See 3 more Smart Citations
“…we observed a wide distribution of neuronal areas for these DA neurons (Figure 2H), which coincides with previous findings that OB DA neuron subtypes may be distinguished by their size (Pignatelli et al, 2005;Kosaka and Kosaka, 2009;Chand et al, 2015;Pignatelli and Belluzzi, 2017;Galliano et al, 2018;Kosaka et al, 2019). Given the previous findings (Halász et al, 1981;Pignatelli et al, 2005;Kosaka and Kosaka, 2007) of differences in soma sizes between two potential populations of OB DA neurons and our finding that neuronal areas of DA neurons are widely distributed (Figure 2H), we also compared these same properties between recorded DA neurons with different sizes ( Table 2).…”
Section: Membrane Propertiessupporting
confidence: 90%
“…Our membrane properties results indicate that there is no preferred glomerular localization of Large and Small DA neurons. However, a recent study by Galliano et al (2018) found that large TH + /DA neurons were mostly expressed in the deep glomerulus, at the border of GL/EPL. Interestingly, these large neurons exclusively possessed an AIS, indicating that these DA neurons are axonic (Galliano et al, 2018).…”
Section: Evidence For and Potential Identity Of At Least Two Types Ofmentioning
confidence: 91%
See 2 more Smart Citations
“…It has also been shown that dopaminergic OB interneurons born at different times give rise to functionally different cell types: whereas interneurons born postnatally are anaxonic and have no axon initial segment, those born during embryonic development have an axon and an axon initial segment, and are more excitable than postnatally generated cells (Galliano et al, 2018). It is unclear whether this is because of the integration of young neurons into a circuit that differs in maturity, whether the age of the niche affects the differentiation of primary progenitors or whether primary progenitors generate different cell types based on their own age.…”
Section: Integrating Signals In Time and Spacementioning
confidence: 99%